Konsumsi Energi, Sarapan Pagi dan Kelelahan Kerja pada Petani Rumput Laut di Desa Ponrang Kecamatan Ponrang - Kaso, Khumaira; Usman, Usman; Umar, Fitriani (Media Literasi Indonesia, 2025)
Work fatigue can be characterized by decreased work performance or all conditions that affect all processes of the organism, including several factors such as feelings of fatigue at work. The purpose of this study was to determine the relationship between energy consumption and work fatigue on seaweed farmers in Ponrang District and the relationship between breakfast and work fatigue on seaweed farmers in Ponrang District. This research method uses quantitative research with a Cross Sectional Study approach with a sample of 75 people, using questionnaires and food recall research instruments. The results of this study were 9 people did not experience fatigue 12%, as many as 23 (30.6%) experienced mild fatigue. A total of 43 (57.3%) experienced severe fatigue and there was a relationship between Energy Consumption and Work Fatigue on Seaweed Farmers in Ponrang District with a p value = 0.028 and there was a relationship between breakfast and work fatigue on seaweed farmers in Ponrang District with a value of p = 0.035.